Review of Budget Resources and Expenditures at the Department of Cooperatives and Micro, Small, and Medium Enterprises (MMSMEs) Enterprises - Rosdiana Nusalelu; Arthur R Tanihatu; Dirk Berly Tehuayo (Univiversitas Dr. Djar Wattiheluw, 2025)
This study examines the comparison between budget realization and budget allocation at the Cooperatives and Small and Medium Enterprises Service of Central Maluku Regency for the fiscal years 2021–2023. Data were collected through interviews and observations of budget sources and realization reports. The findings indicate that the budget is sourced from the Regional Revenue and Expenditure Budget (APBD), with notable discrepancies between allocation and realization each year. In 2021, the realization reached 94.21% of the allocated IDR 5.93 billion; in 2022, it was 97.61% of IDR 8.90 billion; and in 2023, it was 86.93% of IDR 14.41 billion. Overall, the budget allocation showed an upward trend each year, in line with economic development.